Creative Economy Competitiveness Improvement Program for MSMEs in Pangkalpinang City - Darman Saputra; Maya Yusnita; Indah Noviyanti; Nanang Wahyudin; Sumar Sumar; Echo Perdana Kusumah (MOVE: Journal of Community Service and Engagement, 2023)
Deshanda Craft is one of the craft businesses in East Kace Village which has been established since 2018. So researchers want to carry out research with the aim of analyzing the value of the creative economy of craft crafts at Deshanda Craft. The results of the study show that the value contained in Deshanda Craft begins with the creation stage where at this creation stage seeks innovative ideas from the internet and then modifies it to make craft patterns, then the production stage where this production stage manages input or materials in the form of nipa palm sticks as raw materials and into flower vases, baskets, tissue holders for the distribution stage in this Deshanda Craft marketed through online media to factories in the form of wholesalers, and this commercialization stage is through providing information to consumers about the products being marketed.